2023
DOI: 10.1158/1055-9965.epi-22-1257
|View full text |Cite
|
Sign up to set email alerts
|

Infections and Acute Lymphoblastic Leukemia: Is the Sum Worth More than the Parts? Evidence from Birth Characteristics

Abstract: The etiology of childhood acute lymphoblastic leukemia (ALL) has long been studied piecemeal with investigations leading to a lengthy list of putative risk factors including several with immune modulatory effects. The ubiquity of many of these factors (e.g., daycare attendance, low parity, breastfeeding, normal vaccinations) belies the rarity of ALL as an outcome. In this commentary, Pombo-de-Oliveira and colleagues show that a key feature may be the combination of particular risk factors, as the birth charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To date, few risk factors have been found to be associated with childhood leukemia and explain less than 10% of the causes of the disease ( 8 ). One of the regions of Mexico which has been explored further in previous studies is Greater Mexico City (GMC) where it has been reported that the incidence of AL is among the highest in the world ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, few risk factors have been found to be associated with childhood leukemia and explain less than 10% of the causes of the disease ( 8 ). One of the regions of Mexico which has been explored further in previous studies is Greater Mexico City (GMC) where it has been reported that the incidence of AL is among the highest in the world ( 9 ).…”
Section: Introductionmentioning
confidence: 99%